The Global Peace Philosophy. The Right to Intervene – a Case Study - Fligel, Anna (International Studies. Interdisciplinary Political and Cultural Journal, 2022)
The issue of the right to intervene is of a difficult, often controversial nature. Especially when it comes to showing that in many cases – if not entirely at least essentially – this right should be abandoned. This situation takes already place in some sense in international law; even more, it is sometimes acknowledged that within it it is justified to speak about the validity of ius contra bellum (laws against war). Practice is still far from such an ideal. The main goal of this article is to analyze from a normative angle the issue of the right to intervene as one of the most important threads of the global peace philosophy. The article has problematized (counter) arguments used for the right to intervene. Two considered key are, firstly, an argument from the so-called alleged barbarism and secondly, the (counter) argument of the complexity and uniqueness of each case. The article is written mainly from a philosophical and ethical perspective. However, the author also refers to empirical material, mainly in the field of political science, but also to threads in the field of international law, trying to create an interdisciplinary perspective. The selected key issue is also an opportunity to develop the global peace philosophy within the Polish academia. This paper is written with deep conviction that global peace is probably the highest, i.e. a fundamental ideal for humanity, a kind of Summum Bonum.